Estudo comparativo entre os efeitos imunoadjuvantes e inflamatórios dos óleos de oliva, milho e soja - Silva, Ana Cláudia Marinho da (2004)
Since more than a century, a great amount of substances have been used as immunological adjuvants in order to improve the immunization/vaccination, procedures. In spite of that, AI (OHh continues being one of the few licensed adjuvants for hurnan vaccination. The importance of the knowledge of new adjuvants and of your action mechanisms it is evidenced when it is known that, nowadays, the new generation of vaccines will only give good results if supplied with an appropriate adjuvant. To find out the adequate adjuvant. capable to obtain a reliable result in the imunization/vaccination procedures is being an attractive theme for the ones interested in the subject. The use of vegetàble oils as adjuvants is attractive since they are biologically degraded and such effect has already been proven, in spite of the induction of collateral effects of allergic nature. The olive soy and com oils were analyzed chemistry and microbiologicamente and groups of 10 swiss mice were subcutaneously immunized with ovalbumina (OVA. 10 ~g. control) and OVA in NaCI 0,15 M emulsified in rnarcol, AI (OHh, Complete Freund Adjuvante (CFA) or with olive soy or com oils. The mice were bled through the retro-orbital plexus on days 14, 21, 35. 42, 49. 56. 63. 70 and 77 after the first injection. Booster injections were given on days 21 and 35. To evaluate the immunological adjuvant capacity, antibodies anti-OVA (lgG. IgM and IgA) were qauntificados through ELlSA and IgE through Passive Cutaneous Anaphylaxis (PCA) in rats. The inflammatory reaction induced by AI (OH)3, CFA. marcol and by the three vegetable oils was evaluated by the model of the Subcutaneous Air Pouch (SAP) and the migrations of total leucocytes, neutrophyls. macrophages and eosinophyls were quantified. The production of nitric oxide (NO) and the antioxidant capacity of the oils were also determined. Conceming the immunological imunoadjuvant effect of the vegetable oils it can be concluded. that the olive oil has larger adjuvant effect on the imunoglubulinas synthesis (G. A and M) and a smaller effect on the IgE synthesis than that of soy and com oils and it coul be used as a preferential adjuvant in the imunization/vacination procedures. In a general way, the three vegetable oils induced accentuated inflammatory reaction after either 6 or 24 h, although that action has not been uniform and the oils produced by Sigma presented an earlier and more intense inflammatory activity. Due to the variation found in the obtained results, according to the criteria selected to evaluate the inflammatory response (migration of total leucocytes, neutrophyls, macrophages, eosinophyls, production of NO and antioxidant capacity of the oils), it was not still possible to establish, in a quantitative and precise way, the correlation among the two imunologic responses.